Рід Lathyrus (Fabaceae) у флорі України - Крицька, Л.І. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
Приводятся результаты критико-систематической обработки рода Lathyrus L. флоры Украины. Установлено, что в
украинской флоре насчитывается 31 вид рода, принадлежащие к 3 подродам и 16 секциям. Усовершенствована система
рода, сделаны 2 новые комбинации: gen. Lathyrus L., subgen.
1. Lathyrus. (sect. 1. Lathyrus, sect. 2. Rotundifolii Czefr., sect.
3. Apteri (Czefr.) Czefr., sect. 4. Odorati Czefr., sect. 5. Cicercula
(Medik.) Gren. et Godr., sect. 6. Orobastrum Boiss.).
Subgen. 2. Orobus (L.) Peterm. [ sect. 7. Orobus (L.) Gren. et
Godr. (subsect. 1. Раlustres (Bässler) Krytzka, comb. nov., subsect.
2. Nigricantes Czefr.: ser. 1. Nigri Fritsch ex Czefr., ser. 2.
Incurvi Bässler, subsect. 3. Montani Czefr.); sect. 8. Pseudorobus
(Czefr.) Krytzka, comb. nov., sect. 9. Pisiformes (Czefr.) Czefr.,
sect. 10. Eurytrichon Bässler, sect. 11. Pratenses Bässler, sect. 12.
Variiflori (Czefr.) Czefr., sect. 13. Lathyrostylis (Griseb.) Bässler,
sect. 14. Viciopsis Kupicha, sect. 15. Linearicarpus Kupicha, sect.
16. Aphaca (Mill.) Dumort.].
Subgen. 3. Nissolia (Rchb.) Peterm.
Для большинства видов указан номенклатурный тип,
для каждого из них приведены основная синонимика, сведения об экологической приуроченности и географическом
распространении. Предложен ключ для определения видов. The article is devoted to the critically studied genus Lathyrus L.
in the flora of Ukraine. It is ascertained that Ukrainian flora includes
31 species of the genus, belonging to 3 subgenera and 16
sections. The system of the genus was improved and 2 new combinations
are made: gen. Lathyrus L., subgen. 1. Lathyrus. (sect. 1.
Lathyrus; sect. 2. Rotundifolii Czefr., sect. 3. Apteri (Czefr.) Czefr.,
sect. 4. Odorati Czefr., sect. 5. Cicercula (Medik.) Gren. et Godr.,
sect. 6. Orobastrum Boiss.).
Subgen. 2. Orobus (L.) Peterm. [ sect. 7. Orobus (L.) Gren. et
Godr. (subsect. 1. Раlustres (Bässler) Krytzka, comb. nov., subsect.
2. Nigricantes Czefr.: ser. 1. Nigri Fritsch ex Czefr., ser. 2.
Incurvi Bässler, subsect. 3. Montani Czefr.); sect. 8. Pseudorobus
(Czefr.) Krytzka, comb. nov., sect. 9. Pisiformes (Czefr.) Czefr.,
sect. 10. Eurytrichon Bässler, sect. 11. Pratenses Bässler, sect. 12.
Variiflori (Czefr.) Czefr., sect. 13. Lathyrostylis (Griseb.) Bässler,
sect. 14. Viciopsis Kupicha, sect. 15. Linearicarpus Kupicha, sect.
16. Aphaca (Mill.) Dumort.].
Subgen. 3. Nissolia (Rchb.) Peterm.
The nomenclatural types are given for majority of species, the
synonymy and information about ecological conditions and geographical
distribution are provided for each species. The key for
identification of species are given.